Predictable dental rehabilitation in maxillomandibular reconstruction with free flaps. The role of implant guided surgery - Cebrian-Carretero, José L. (Med Oral Patol Oral Cir Bucal, 2014)
The reconstruction of maxillomandibular defects secondary to oral cancer surgery, represent a great challenge for Maxillofacial surgeons. During the last decades the reconstructive surgery has experimented a big advance due to the development of the microsurgical techniques. At present, we are able to reconstruct complex defects using free flaps that provide both soft and bone tissue. Fibula, iliac crest and scapula free flaps have been the three classic options for the maxillomandibular reconstruction owing to the amount of bone that this flaps provide, allowing the posterior dental rehabilitation with implants. Today, our objective it is not only the aesthetic reconstruction, but also the functional reconstruction of the patients enhancing their life quality. Guided implant surgery in free flap reconstructed patients has become an essential tool, helping to define the exact position of the dental implant in the flap. In this way it is possible to look for the areas with better bone conditions, avoiding the osteosynthesis material used to fixate the flap with the native bone and deciding the best biomechanical option, in terms of number and situation of the implants, for the future dental prostheses. In summary, using the guided implant surgery, it is possible to design an exact and predictable dental implant rehabilitation in patients with oral cancer who are reconstructed with free microvascular flap, resulting in an optimal aesthetic and functional result. Key words:Oral cancer, mandibulectomy, maxillectomy, microvascular reconstruction, fibula flap, dental implant, guided surgery.